Factors Influencing Customer Impulse Buying Behavior in Apparel Live Streaming Commerce in China: The Role of Customer Inspiration - Ping, Ma; Rani, Shamsul Huda Binti Abd; Yusof, Mohd Sufli Bin (International Review of Management and Marketing, 2026)
Live-streaming commerce has changed global consumer behavior dramatically recent years, especially in China. This study explores the influence of social presence and perceived novelty on impulse buying behavior by the mediating role of customer inspiration. Stimulus‒organism‒response (S-O-R) model is employed to create a theoretical framework. 396 respondents completed a questionnaire that gathered information on constructions and demographics. The hypotheses and mediation effect were evaluated in this study using partial least squares structural equation modeling (PLS-SEM). The results show that perceived novelty and social presence both have a positive influence on impulsive purchasing behavior, with customer inspiration serving as a key mediator. By emphasizing the significance of consumer inspiration in boosting impulsive purchasing behavior in apparel live streaming commerce, this study contributes to the literature. The findings have practical implications for streamers, suggesting the need for specialized marketing strategies and services based on customers preferences.